2020
DOI: 10.3390/s20030757
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Derived Feasibility of Optical Camera Communications under Turbulence and Fog Conditions

Abstract: Optical camera communications (OCC) research field has grown recently, aided by ubiquitous digital cameras; however, atmospheric conditions can restrict their feasibility in outdoor scenarios. In this work, we studied an experimental OCC system under environmental phenomena emulated in a laboratory chamber. We found that the heat-induced turbulence does not affect our system significantly, while the attenuation caused by fog does decrease the signal quality. For this reason, a novel strategy is proposed, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
20
0
3
Order By: Relevance
“…Consequently, the PDs of the pixels exposed for a shorter time have a lower signal-to-noise ratio (SNR). In previous works, it was shown that the reduced received power due to the extinction along the path or due to low exposure times can be overcome using the analogue amplifier of the CMOS camera by increasing the gain it provides before the analogue-to-digital converter (ADC), ultimately improving the SNR [ 20 , 21 ].…”
Section: Proposed Architecturementioning
confidence: 99%
“…Consequently, the PDs of the pixels exposed for a shorter time have a lower signal-to-noise ratio (SNR). In previous works, it was shown that the reduced received power due to the extinction along the path or due to low exposure times can be overcome using the analogue amplifier of the CMOS camera by increasing the gain it provides before the analogue-to-digital converter (ADC), ultimately improving the SNR [ 20 , 21 ].…”
Section: Proposed Architecturementioning
confidence: 99%
“…Nonetheless, these approaches are impractical if it is considered that the FOV of the receiver optics is drastically reduced. As a solution for maintaining the camera’s original FOV, in previous works [ 15 , 16 ] it is demonstrated that the signal attenuation produced by turbulence and fog phenomena can be overcome by increasing the analog gain of the image sensor without the need to alter the camera optics.…”
Section: Related Workmentioning
confidence: 99%
“…Further experimentation has been carried out, including the effects of heat-induced turbulence and exploiting the camera’s analog gain in [ 15 , 16 ]. Real conditions of a sandstorm were experimentally studied in [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average BER of the maritime VLC system under oceanic turbulence was evaluated in [ 14 ], and it was found that the BER decreased with increasing aperture size and wavelength, and increased with oceanic turbulence and link span. In [ 15 ], the effects of fog and weak AT on a VLC link with a camera-based optical receiver (Rx) were investigated using Pearson’s correlation coefficient with reference to a template signal. The results obtained showed that under weak AT there was no significant change in the signal quality.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained showed that under weak AT there was no significant change in the signal quality. In [ 11 ], we experimentally investigated the effects of higher AT strengths with AA than in [ 15 ], up to of 1.1 × 10 –10 m −2/3 in vehicular VLC (VVLC) with a camera-based Rx for two camera gain factors (i.e., low and high). Results showed that the peak SNR (PSNR) performance (i.e., an image quality metric) of the link was not significantly degraded by AT with AA for both gain factors investigated.…”
Section: Introductionmentioning
confidence: 99%